Analisis Sosiokulturalterhadap Peningkatan Tindak Pidana Kekerasan dalam Rumah Tangga (KDRT) Sebagai Dampak Pandemi Covid-19 di Wilayah Kabupaten Cianjur - Mia Amalia (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
The application of social distancing or self-quarantine at home in reducing the pandemic causes people to stay at home every day. On the one hand, the application of social distancing has a positive impact on the health sector in reducing the spread of the corona virus, but in the economic field it makes it difficult for people to work and earn income. Socially, there are domestic problems with increasing cases of Domestic Violence (KDRT). So in this writing there are several problems and objectives in this study, namely the increase in domestic violence (KDRT) as a result of the Covid-19 pandemic, as an effort to overcome the increase in domestic violence during the pandemic. The research method is to use empirical legal research methods. The impact of increasing domestic violence with the presence of covid due to lack of faith and patience, inadequate financial conditions, unstable economy, perpetrators and victims being in one house (being laid off) have resulted in increased violence, both physical, psychological or neglect of the family, as well as a patriarchal culture . So to overcome this, an increase in faith and devotion, legal counseling for the community, an increase in synergy integrated services for each related agency was carried out.